Niklas Luhmann and the Risks of Moral Communication: Polemogeny and Modernity - Lovasz, Adam (International Journal of Mass Communication, 2026)
Niklas Luhmann’s systems theory offers a radical rethinking of morality and society, conceptualizing the latter not as a collection of human beings grounded on a moral consensus, but rather as a collection of operationally closed systems of communications. Within this framework, morality is identified as a specific, highly volatile form of communication characterized by the binary code of respect and disrespect, or esteem and disesteem. This medium does not integrate modern society in the way classical thinkers within the sociological tradition such as Émile Durkheim imagined. Rather, in a world defined by the evolution of functional differentiation, morality assumes a provocative "alarm function" that frequently generates more conflict than it resolves, a condition Luhmann identifies as inherently "polemogenous". As a remedy to the contemporary overproduction of moral discourse and moral panics, I propose that a Luhmannian approach must emphasize pluralism and the autonomy of systems.